ANALISIS FAKTOR YANG MEMPENGARUHI PERMINTAAN RUJUKAN PASIEN BPJS KESEHATAN DI PUSKESMAS NGKERAN KECAMATAN LAWE ALAS KABUPATEN ACEH TENGGARA TIMUR TAHUN 2019 - Sinaga, Jon; Sitio, Sri Sudewi (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
Health services received by BPJS participants are carried out through a tiered referral mechanism, which is a definition of a health service referral system that regulates the delegation of duties and responsibilities of health services both vertically and horizontally. The purpose of this study was